2021
DOI: 10.3390/cancers13236068
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Arginine Metabolism in Oral Tongue Squamous Cell Carcinoma

Abstract: Early diagnosis and treatment do not prevent the high morbidity and poor prognosis of oral tongue squamous cell carcinoma (TSCC). Earlier studies have shown that ARG1 signaling is deregulated in TSCC. Here, we investigated the complexity of ARG1 metabolism in this cancer subsite to appreciate the therapeutic potential of this potential biological vulnerability. Various functional studies show that ARG1 overexpression in oral cancer cells inhibits cell proliferation and invasion compared with controls. Further,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Recent studies confirmed a close link between OSCC and metabolites, which may provide new perspectives and new potential targets for the diagnosis and treatment of OSCC[ 10 , 11 ]. Tumor metabolism is associated with tumor cell proliferation, survival, and antitumor immunity in the tumor microenvironment (TME)[ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies confirmed a close link between OSCC and metabolites, which may provide new perspectives and new potential targets for the diagnosis and treatment of OSCC[ 10 , 11 ]. Tumor metabolism is associated with tumor cell proliferation, survival, and antitumor immunity in the tumor microenvironment (TME)[ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%